The Effectiveness of Using Realistic Mathematic Education and Problem Posing Approach on Increasing the Ability to Solve Fraction Story Questions for Grade IV of SDIT Annur, Central Cikarang District, Bekasi Regency - Cepy Kurniawan; Maximus Gorky Sembiring; Juhana Juhana (Universitas Muhammadiyah Enrekang, 2024)
This research aims to determine differences in the effectiveness of realistic mathematic education (RME) and problem posing (PP) approach viewed from the ability to solve fraction story questions for grade IV students. The sampling technique is carried out by: simple random sampling. The population is all grade IV students of SDIT Annur, Central Cikarang District, Bekasi Regency, academic year of 2023/2024. This type of research is a quasi-experiment which uses 2 randomly selected sample classes namely the experimental class with the RME learning approach and the control class with the PP approach. The instruments used in collecting data in this research are an observation sheet and tests. Data collection is carried out by means of observation, tests and documentation. Data analysis was carried out using quantitative descriptive. The research results show that the paired t-test value in the intervention group showed P-value = 0.000, meaning that the RME approach increases the ability to solve fraction story problems. T-test 2 free sample P-value = 0.000, with mean in the intervention group 90.7500 and the control group 72.0000. Thus, the RME approach is more effective than PP in improving the ability to solve fraction story problems.